2012
DOI: 10.1097/prs.0b013e3182362171
|View full text |Cite
|
Sign up to set email alerts
|

Composite Extremity and Trunk Reconstruction with Vascularized Fibula Flap in Postoncologic Bone Defects

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…There were 2 cases of delayed flap fracture caused by external trauma, both of which presented with normal consolidation after orthopedic fixation. The mean time to ambulation was 14.2 months, similar to those of global reports 2,19,20 . The mean flap size in this study was 15.8 cm (range, 10-20 cm).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There were 2 cases of delayed flap fracture caused by external trauma, both of which presented with normal consolidation after orthopedic fixation. The mean time to ambulation was 14.2 months, similar to those of global reports 2,19,20 . The mean flap size in this study was 15.8 cm (range, 10-20 cm).…”
Section: Discussionsupporting
confidence: 74%
“…In this series, we used the allograft in one case, in which ambulation occurred 10 months after surgery. Clemens et al 20 recently demonstrated a higher rate of con solidation and therefore earlier rehabilitation when only the free flap was used compared to the allograft/free flap (100% vs. 82.4%) and recommended the use of this kind of reconstruction in cancer patients. In this series, 100% of the flaps were viable, there was excellent integration of the flap to the receptor site, and there were no cases of pseudoar throsis or nonconsolidation.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, in most series looking at allografts compared with vascularized grafts, there are increased bony nonunion rates in patients with allograft-vascularized grafts (85.2 percent) compared with patients with vascularized grafts alone (100 percent). 11 Moreover, Moran et al showed in their series of pediatric patients that all nonunions occurred in patients who underwent postoperative chemotherapy. 12 In our series, 83.3 percent (n = 10) of patients underwent both preoperative induction chemotherapy and postoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…First, there are significant limitations associated with the large-segment allografts. [10][11][12] Large-segment allografts heal through osteoconduction.…”
Section: Discussionmentioning
confidence: 99%
“…Whether because of trauma or resection secondary to tumors, this type of bone loss 24 can be reconstructed with free bone flaps. However, when there is also associated loss of tissue, such as muscle or skin, the repair requires greater tissue contribution.…”
mentioning
confidence: 99%